HIGH BLOOD / MILK UREA NITROGEN HAD DELETERIOUS IMPACT ON FERTILITY PARAMETERS IN CROSSBRED COWS - ANAND, I; DHALIWAL, G S; CHAWLA, P S (The Indian Journal of Animal Reproduction, 2022)
Eighty-two healthy and recently calved crossbred cows from seven dairy farms were subjected to monthlyblood and milk sampling for a four-month period for blood and milk urea nitrogen (BUN/MUN) assessment. Thefertility parameters like calving to first estrus interval, calving to first service interval, calving to conception interval,services per pregnancy and percent animal conceived were recorded. The cows with high BUN or MUN hadsimilar number of days to exhibit estrus and to first service compared to their counterparts (p>0.05). The cows withlow BUN or MUN had lesser number of days to conceive than those with high BUN (p0.05). Thepercent animals conceived followed a similar trend in both BUN and MUN groups; low level groups had higher(p
Keywords: BUN; Crossbred cows; Fertility; MUN; Protein